Effects of increasing GleptoForte dosage in newborn piglets - Schmidt, Darby L.; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
The use of iron supplementation in newborn piglets is well known and iron deficiency can effect a newborn piglet’s growth rate. Yet, it is unknown the proper level of iron injection to provide newborn piglets and the proper booster. The objective of this experiment is to determine the effects of GleptoForte dosage, nursey growth performance and hematological parameters on nursing piglets. This 21-day experiment included 336 newborn piglets used to evaluate an increasing dosage of GleptoForte in a farrowing study. The negative control was no iron injection. The iron injection treatments included: 1) 50 mg; 2) 100 mg; 3) 150 mg; 4) 200 mg; and 5) 200 mg plus a 100 mg booster. All piglets were weighed on d3, and six barrows and six gilts from each litter were selected randomly to the treatments. There were 56 piglets per treatment. Data was collected through blood collection through the jugular venipuncture on d3, d11, and d21 on one barrow per treatment per litter. Hemoglobin, hematocrit, serum Fe, and total iron binding capacity were measured. Average daily gain (ADG) and body weight (BW) were also measured. The results of the experiment led to the conclusion that the piglets’ ADG improved (quadratic; P = 0.002) with an increasing dosage of GleptoForte. BW also improved (quadratic; P = 0.018) with an increasing dosage of GleptoForte. There was no evidence of an increase in ADG or BW between the iron injection dosage of 200 mg and the 200 mg + 100 mg booster dosage. This suggests there is no additional benefits of an iron injection booster. There was no evidence of a change observed on d3 of hematological levels. On d11 and d21 200 mg treatment had the highest hematological levels and the negative control had the lowest levels. On d21 there was a significant difference (P =0.011) in hematological levels in the 200 mg and 200 mg+100 mg treatments. The 200 mg+100 mg was larger. In summary, the negative control of no iron injection led to the poorest growth and lowest blood data. The 100 mg iron injection treatment resulted in the highest performance in growth. There was no difference in improvement between the 200 mg treatment and the 200 mg+ 100 mg booster when it came to growth performance.
Keywords: Fall 2017